Flow Cytometric and Microscopic Analysis of the Effect of Tannic Acid on Plant Nuclei and Estimation of DNA Content - LOUREIRO, JOÃO (Oxford University Press, 2006)
• Background and Aims Flow cytometry (FCM) is extensively used to estimate DNA ploidy and genome size in plants. In order to determine nuclear DNA content, nuclei in suspension are stained by a DNA-specific fluorochrome and fluorescence emission is quantified. Recent studies have shown that cytosolic compounds may interfere with binding of fluorochromes to DNA, leading to flawed data. Tannic acid, a common phenolic compound, may be responsible for some of the stoichiometric errors, especially in woody plants. In this study, the effect of tannic acid on estimation of nuclear DNA content was evaluated in Pisum sativum and Zea mays, which were chosen as model species. • Methods Nuclear suspensions were prepared from P. sativum leaf tissue using four different lysis buffers (Galbraith's, LB01, Otto's and Tris.MgCl(2)). The suspensions were treated with tannic acid (TA) at 13 different initial concentrations ranging from 0·25 to 3·50 mg mL(−1). After propidium iodide (PI) staining, samples were analysed using FCM. In addition to the measurement of nuclei fluorescence, light scatter properties were assessed. Subsequently, a single TA concentration was chosen for each buffer and the effect of incubation time was assessed. Similar analyses were performed on liquid suspensions of P. sativum and Z. mays nuclei that were isolated, treated and analysed simultaneously. FCM analyses were accompanied by microscopic observations of nuclei suspensions. • Key Results TA affected PI fluorescence and light scatter properties of plant nuclei, regardless of the isolation buffer used. The least pronounced effects of TA were observed in Tris.MgCl(2) buffer. Samples obtained using Galbraith's and LB01 buffers were the most affected by this compound. A newly described ‘tannic acid effect’ occurred immediately after the addition of the compound. With the exception of Otto's buffer, nuclei of P. sativum and Z. mays were affected differently, with pea nuclei exhibiting a greater decrease in fluorescence intensity. • Conclusions A negative effect of a secondary metabolite, TA, on estimation of nuclear DNA content is described and recommendations for minimizing the effect of cytosolic compounds are presented. Alteration in light scattering properties of isolated nuclei can be used as an indicator of the presence of TA, which may cause stoichiometric errors in nuclei staining using a DNA intercalator, PI.